2010
DOI: 10.4103/0970-2113.63613
|View full text |Cite
|
Sign up to set email alerts
|

Basidiobolus: An unusual cause of lung abscess

Abstract: Non-resolving pneumonia leading to lung abscess is always a challenge to the treating physician especially in a diabetic patient. Atypical radiological features of lung abscess should raise the suspicion of unusual organisms. This is a case report of a 42 year old diabetic male presented with features suggestive of lung abscess and multiple target organ damage. Subsequent work up revealed that the etiological agent is a rare fungus – Basidiobolus. To the best of our knowledge this is the first case of Basidiob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…In the present study, during a period of 9 months, 18 cases of lung abscess were observed, in contrast to other studies: In Taiwan, a 20-year study found 23 cases of lung abscess (5) ; In Iran in 15 years, there were 22 cases (6) ; In Houston in 11 years there were 45 cases (7) and in India, 1 case in 1 year (8) . This finding in the present study demonstrates the trend of increasing cases of lung abscess as a complication of pneumonia in the community, or by aspiration of foreign bodies, in Luanda (Angola) where socioeconomic conditions favor the development of the disease.…”
Section: Discussioncontrasting
confidence: 95%
“…In the present study, during a period of 9 months, 18 cases of lung abscess were observed, in contrast to other studies: In Taiwan, a 20-year study found 23 cases of lung abscess (5) ; In Iran in 15 years, there were 22 cases (6) ; In Houston in 11 years there were 45 cases (7) and in India, 1 case in 1 year (8) . This finding in the present study demonstrates the trend of increasing cases of lung abscess as a complication of pneumonia in the community, or by aspiration of foreign bodies, in Luanda (Angola) where socioeconomic conditions favor the development of the disease.…”
Section: Discussioncontrasting
confidence: 95%
“…Basidiobolus was first described by Eidam in 1886. It is a filamentous fungus isolated from amphibians, reptiles, horses, dogs and bats, as well as wood lice, plant debris and soil . Basidiobolus is classified into B. ranarum, B. meristosporus and B. haptosporus .…”
Section: Basidiobolomycosismentioning
confidence: 99%
“…Phototrophic property of these fungi [26] is hypothesized to facilitate subcutaneous localization of the spores. Occasional cases of lung [15] and gut [7,10] infections support the hypothesis of aerodigestive inoculation. In our series only 38% had identifiable incident of potential transcutaneous inoculation.…”
Section: Discussionmentioning
confidence: 81%
“…In Burkitt's series 63% of patients were under the age of 9 and 30% were adolescents while only 7% were adults [2]. The infection is mostly confined to subcutaneous tissue, although, disseminated forms [12][13][14] and visceral involvement [10,15] are rarely reported. Even in endemic areas, subcutaneous EM is frequently mistaken for soft tissue sarcoma or lymphoma [6,16,17].…”
mentioning
confidence: 96%